2018
DOI: 10.1007/s11192-018-2866-8
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinarity and insularity in the diffusion of knowledge: an analysis of disciplinary boundaries between philosophy of science and the sciences

Abstract: Two fundamentally different perspectives on knowledge diffusion dominate debates about academic disciplines. On the one hand, critics of disciplinary research and education have argued that disciplines are isolated silos, within which specialists pursue inward-looking and increasingly narrow research agendas. On the other hand, critics of the silo argument have demonstrated that researchers constantly import and export ideas across disciplinary boundaries. These perspectives have different implications for how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Furthermore, as we demonstrate elsewhere, there is evidence to suggest that philosophers' broader impacts are much more likely to come from face-to-face engagement with other communities than by publishing in philosophy journals alone (see Plaisance et al 2019). Our citation study revealed something similar: for the most part, when it comes to citing publications by philosophers of science, scientists tend to cite those publications that appear in science journals, while other philosophers are more likely to cite publications appearing in philosophy journals (McLevey et al 2018). This lack of disciplinary cross-over suggests that disseminating one's work to scientific communities is essential for philosophers of science who wish to have their work taken up in scientific domains.…”
Section: An Emerging Picture Of Philosophy Of Sciencementioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, as we demonstrate elsewhere, there is evidence to suggest that philosophers' broader impacts are much more likely to come from face-to-face engagement with other communities than by publishing in philosophy journals alone (see Plaisance et al 2019). Our citation study revealed something similar: for the most part, when it comes to citing publications by philosophers of science, scientists tend to cite those publications that appear in science journals, while other philosophers are more likely to cite publications appearing in philosophy journals (McLevey et al 2018). This lack of disciplinary cross-over suggests that disseminating one's work to scientific communities is essential for philosophers of science who wish to have their work taken up in scientific domains.…”
Section: An Emerging Picture Of Philosophy Of Sciencementioning
confidence: 71%
“…We report the results of that research elsewhere (Plaisance et al 2019), though we do mention some of our qualitative findings below to provide context for the survey data. Furthermore, knowing that both surveys and interviews rely on self-report, our project also includes a bibliometric study of the citation patterns of philosophy of science articles in order to better understand broader uptake of philosophical work (McLevey et al 2018).…”
mentioning
confidence: 99%
“…The advantages and disadvantages of the disciplinary structure for advancement of sciences are currently much discussed, with conclusions that favour interdisciplinarity for the advancement of sciences [62,63,71,82,85,86]. However, the degree to which interdisciplinarity is realized, and even its benefits, are questioned and disputed [87].…”
Section: Interdisciplinarity and Knowledge Flowsmentioning
confidence: 99%
“…Therefore, we decided to use WOS for our data needs. As a curated collection of scientific scholarly content, WOS's level of bibliometric coverage of scientific literature is very similar to that offered by other licensed indexing services (McLevey et al 2018).…”
Section: Publication Databasementioning
confidence: 99%